2011
DOI: 10.1007/s11090-010-9285-9
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Excitation of CN Molecules in He–CO–N2–O2 Discharge Plasmas

Abstract: The emission by electronically excited CN molecules is a prominent feature in the spectrum of active nitrogen containing traces of carbonaceous species. A large amount of experimental work has been devoted to an investigation of CN emission. However, up to now the plasma chemistry of CN radicals and processes leading to the excitation of CN electronic states are still poorly understood. The results of experimental measurements and numerical simulations are compared in order to establish the role of various cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It can be seen that the measured and calculated values agree very well. Plasma-chemical processes determining CN concentration are described in [9] in detail. It was found that the CN molecules under conditions characteristic for discharge plasma of CO lasers are produced in processes…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be seen that the measured and calculated values agree very well. Plasma-chemical processes determining CN concentration are described in [9] in detail. It was found that the CN molecules under conditions characteristic for discharge plasma of CO lasers are produced in processes…”
Section: Resultsmentioning
confidence: 99%
“…Experimental set-up has been described already in a previous work [9]. The water-cooled discharge tube from molybdenum glass, 17 mm in diameter, was used in the experiment.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…21 The chemical processes that take place inside the discharge are still an active field of research: probable reaction chains for the formation and excitation of the CN molecule in a He-CO-N 2 -O 2 discharge plasma have been described in the literature, but "up to now the plasma chemistry of CN radicals and processes leading to the excitation of CN electronic states are still poorly understood". 22 …”
Section: Methodsmentioning
confidence: 99%